Functional Fc gamma receptor gene polymorphisms and long-term kidney allograft survival - Wahrmann, Markus; Döhler, Bernd; Arnold, Marie-Luise; Scherer, Sabine; Mayer, Katharina A.; Haindl, Susanne; Haslacher, Helmuth; Böhmig, Georg A.; Süsal, Caner (Frontiers in immunology, 2021)
The functional Fc gamma receptor (FcγR) IIIA polymorphism FCGR3A-V/F158 was earlier suggested to determine the potential of donor-specific HLA antibodies to trigger microcirculation inflammation, a key lesion of antibody-mediated renal allograft rejection. Associations with long-term transplant outcomes, however, have not been evaluated to date. To clarify the impact of FCGR3A-V/F158 polymorphism on kidney transplant survival, we genotyped a cohort of 1,940 recipient/donor pairs. Analyzing 10-year death-censored allograft survival, we found no significant differences in relation to FCGR3A-V/F158. There was also no independent survival effect in a multivariable Cox model. Similarly, functional polymorphisms in two other activating FcγR, FCGR2A-H/R131 (FcγRIIA) and FCGR3B-NA1/NA2 (FcγRIIIB), were not associated with outcome. There were also no significant survival differences among patient subgroups at increased risk of rejection-related injury, such as pre-sensitized recipients (> 0% panel reactivity; n = 438) or recipients treated for rejection within the first year after transplantation (n = 229). Our study results suggest that the earlier shown association of FcγR polymorphism with microcirculation inflammation may not be strong enough to exert a meaningful effect on graft survival.